THE SCHOOL INCLUSION PROCESS IN PHYSICS TEACHING: THE USE OF EDUCATIONAL OBJECTS AND ITS CONTRIBUTIONS - Melques, Paula Mesquita [UNESP]; Schlunzen Junior, Klaus [UNESP]; Osorio Araya, Ana Maria [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias & Tecnologia, 2015)
This paper presents a Master research which investigates the contribution of the use of Educational Objects (EO) to the inclusion process on Physics classes. It was studied how the EO can be used in Physics classes; analyzed and selected the EO which contemplate the Physics contents and can contribute to the process of school inclusion, and also investigate if the selected Educational Objects contribute to the inclusion of students with intellectual disability on the process of teaching and learning Physics. This research is qualitative and focused on intervention research methodology. The study was conducted in a public school in Presidente Prudente, interior of Sao Paulo State. According to the results, it was concluded that the use of Educational Objects contributed to the process of school inclusion in Physics teaching in the context of this research.
Keywords: Educational Objects; Physics Teaching; School Inclusion; Intellectual Disability